TROMBOSE VENOSA EXPERIMENTAL NA COBAIA: EFEITO DA HEPARINA E DE DROGAS QUE ALTERAM A FUNCAO PLAQUETARIA - Maffei, Francisco Humberto de Abreu [UNESP]; Pinto, A. M.; Fabris, Viciany Erique [UNESP]; Lastória, S.; Rollo, H. D. (My University, 1977)
Thrombosis was induced in the jugular vein of guinea pigs by damage of the epithelium with a sclerosing solution. The effect of heparin, Dextran 70, acetylsalicylic acid, dipyridamole and phenylbutazone in preventing the development of the thrombus was investigated. Only heparin in high doses showed this effect.
Experimental venous thrombosis in guinea pigs: effect of heparin and drugs affecting platelet function
Keywords: acetylsalicylic acid; dextran 70; dipyridamole; heparin; phenylbutazone; animal experiment; blood and hemopoietic system; drug efficacy; guinea pig; jugular vein; thrombocyte aggregation; thrombosis; Animals; Anti-Inflammatory Agents; Anticoagulants; Aspirin; Blood Platelets; Dextrans; Dipyridamole; Drug Evaluation; Guinea Pigs; Heparin; Phenylbutazone; Thrombophlebitis